Desalination Technique on Seaweeds Hydrolysate Eucheuma Cottonii for Bioethanol Production - Jaini Fakhrudin; Dwi Setyaningsih; Mulyorini Rahayuningsih (International Journal of Engineering, Science and Information Technology, 2021)
The dissolved salts on Eucheuma cottonii hydrolysate interfere the growth of S. cerevisiae in the fermentation as it is considered as inhibitors. These salts are derived from biomass and formed from the chemicals used for hydrolysis processes such as H2SO4 and CaOH2. Ions and cations of the salts are potential as inhibitors such as Na+, Cl-, NH4+, SO42-. Osmotic pressure is raised due to the presence of salt. The efforts had been made to reduce salinity level through electrodialysis. The objective of this study was to eliminate dissolved salts in the hydrolysate in order to optimize the process of fermentation and increase ethanol yield. The results showed that the process of desalination by electrodialysis was able to reduce the salinity of 20% on the voltage of 5 V for 30 minutes; the voltage 9 V for 15 minutes; the voltage 12 V for 30 minutes. The lowest decline of SO42- occurred at treatment of 12 V for 45 minutes. The content of sulfate in the treatment decreased to 2.97 g/l or 46.22%. The more sulfate is reduced through the electrodialysis process, the better the fermentation process is carried out. Desalination treatment at a voltage of 5 V for 30 minutes had been the best treatment because it    produced the highest ethanol yield of 2.06%. All the voltage treatments and the length of time on the electrodialysis process had a significant influence on the levels of ethanol yield. The process of desalination by electrodialysis was able to reduce the levels of dissolved salts, then it had a significant effect on ethanol yield.